2013
DOI: 10.3109/03639045.2012.752502
|View full text |Cite
|
Sign up to set email alerts
|

Biological artificial fluid-induced non-lamellar phases in glyceryl monooleate: the kinetics pathway and its digestive process by bile salts

Abstract: All the results concluded that temperature, pH and ionic strength tendencies for the formation of non-lamellar structures greatly influenced the self-assembly process, thereby affecting the final mesophase structure. The results of this study are important to understand the lamellar to non-lamellar lipid-phase transitions and their possible pharmaceutical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…18,77 Phospholipids, in particular, are known to compete for the oil-water interface, which may have resulted in displacement of interfacial crystals or other surface-active species. 51,71,73,84 This phenomenon was particularly visible for the GMS and GMO-F emulsions as remnants of empty GMS shells were observed (Figure 19A The microstructure of the PGPR-F emulsion showed evidence of emulsion droplets even after 120 min of contact the Condition 3 -SIF (Figure 19F), though there was also extensive aggregation, suggesting that the fat crystal network was effective at protecting the dispersed phase from attack by the bile salts. It has been reported that bile salts interact with fats, emulsifying them and facilitating their breakdown into MAGs and free fatty acids via pancreatic lipase.…”
Section: Effect Of Environment On Mb Releasementioning
confidence: 96%
See 3 more Smart Citations
“…18,77 Phospholipids, in particular, are known to compete for the oil-water interface, which may have resulted in displacement of interfacial crystals or other surface-active species. 51,71,73,84 This phenomenon was particularly visible for the GMS and GMO-F emulsions as remnants of empty GMS shells were observed (Figure 19A The microstructure of the PGPR-F emulsion showed evidence of emulsion droplets even after 120 min of contact the Condition 3 -SIF (Figure 19F), though there was also extensive aggregation, suggesting that the fat crystal network was effective at protecting the dispersed phase from attack by the bile salts. It has been reported that bile salts interact with fats, emulsifying them and facilitating their breakdown into MAGs and free fatty acids via pancreatic lipase.…”
Section: Effect Of Environment On Mb Releasementioning
confidence: 96%
“…It has been reported that bile salts interact with fats, emulsifying them and facilitating their breakdown into MAGs and free fatty acids via pancreatic lipase. 73,77,[85][86][87] Hence, the release trends seen in Figure 18 may be explained by the slow breakdown of fat facilitated by the bile salts over time, especially for the fat-containing emulsions (GMO-F and PGPR-F). This was not the case with the PGPR-only emulsion, where after 60 and 120 minutes, complete emulsion breakdown had taken place (Figure 19G and H), a further testament to the stabilizing role of the fat crystal network.…”
Section: Effect Of Environment On Mb Releasementioning
confidence: 99%
See 2 more Smart Citations
“…GMO was proved as excipients for oral administration in many countries (Nardin & K€ ollner, 2019). It could be cleaved by pancreatic lipase into oleic acid and glycerol, due to the ester bond in GMO (Zhou et al, 2014). Therefore, the biosafety of oral administration of SPTSs could be secured.…”
Section: Introductionmentioning
confidence: 99%